Zero‐current switching method for dc–dc buck converter in portable application. Issue 23 (1st November 2015) - Zhang, Haozhou; Zhao, Menglian; Wu, Xiaobo
Abstract : A novel zero‐current switching (ZCS) method for dc–dc buck converter is proposed. Instead of a conventional high precision and high speed comparator, a comparator with adaptive offset is designed here. By detecting the conduction of parasitic body diode after low‐side power transistor turned off, the offset is automatically adjusted to achieve ZCS. Thus the delay and offset of comparator are no longer an obstacle in circuit design and the measurement results show that the turned‐off inductor current is <10 mA, 1% of the peak value of inductor current and its power consumption is no larger than traditional ones.